2013
DOI: 10.5152/akd.2013.263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardio-ankle vascular index in patients with cardiac syndrome-X: an observational study

Abstract: Objective: Arterial stiffness is associated with major adverse cardiovascular events. Cardio-ankle vascular index (CAVI), a novel marker of arterial stiffness, which is weakly influenced by systolic blood pressure, is a sensitive marker the atherosclerosis and arteriolosclerosis. The aim of this study is to investigate arterial stiffness by CAVI in patients with cardiac syndrome X (CSX). Methods: The present study was observational and cross sectional, and involved 49 patients (26 male) with CSX (angina-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…When we explored the 13 studies comparing CAVI values in individuals with and without CVD, the pooled mean difference in CAVI values was significantly positive at 1.28 (0.86‐1.70) (Figure ). This pattern was generally consistent for coronary heart disease and stroke (Table ). The funnel plot for the mean difference in CAVI values against their standard errors did not indicate publication bias (Figure ).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…When we explored the 13 studies comparing CAVI values in individuals with and without CVD, the pooled mean difference in CAVI values was significantly positive at 1.28 (0.86‐1.70) (Figure ). This pattern was generally consistent for coronary heart disease and stroke (Table ). The funnel plot for the mean difference in CAVI values against their standard errors did not indicate publication bias (Figure ).…”
Section: Resultssupporting
confidence: 63%
“…Despite varying definitions of CVD across studies (Table ), all 17 studies reported significant associations between CAVI and CVD (Table ) . When we explored the 13 studies comparing CAVI values in individuals with and without CVD, the pooled mean difference in CAVI values was significantly positive at 1.28 (0.86‐1.70) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAVI is associated with epicardial fat thickness, atherosclerosis, chronic obstructive lung disease, coronary syndrome-x, dipping status, silent neuronal injury, diabetes, aging, chronic renal failure, dyslipidemia, smoking, hypertension, and obstructive sleep apnea. [14][15][16][17][18][19] Additionally, vasoactive medications including alpha-blockers, betablockers, angiotensin-converting enzyme inhibitors also alter CAVI. 19 None of our patient used antihypertensive medications in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, its limited sensitivity and specifi city lead to suboptimal performance in many cases which can raise indirect costs: inconclusive tests generally necessitate additional exams, which increases the overall cost of the diagnostic strategy; false negative results can delay or prevent correct diagnosis, while false positive results frequently require more complex and costly non-invasive exams or result in unnecessary diagnostic catheterization, which entails risks and potentially avoidable cost (4) . Evaluation of epicardial fat thickness, ankle brachial index, carotid intima media thickness, aortic stiffness, coronary calcium score and oxidative stress may confer further risk stratifi cation (5)(6)(7)(8)(9)(10)(11) It is recommended to continue further imaging stress test to patients with intermediate results and low-intermediate pretest probability (1) . CCTA is a promising non-invasive anatomical test for the evaluation of stable coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%